The amygdala : A discrete multitasking manager / Barbara Ferry - Ferry, Barbara
Among the components of the limbic system, the amygdala is a fascinating structure that is involved in the processes of liking and disliking and in the ways our emotions drive our actions and affect the strength of our memories.